Komposisi dan Kelimpahan Makrozoobenthos Krustasea di Kawasan Vegetasi Mangrove Kel. Tugurejo, Kec. Tugu, Kota Semarang - Ulum, Muchammad Miftahul; Widianingsih, Widianingsih; Hartati, Retno (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Mangrove forests are unique ecosystems, due to a combination of habitat caused by land and sea. Mangrove ecosystem is also the life of various animal species, including crustaceans benthos plays an important role in the ecosystem. The change of land use for a wide range of human interests are expected to affect the abundance krustaseayang conditions contained in the region. The study was conducted in September 2011 - March 2012. This research is descriptive. Sampling was done by two methods, ie. qualitative (in 5x5 meter2) and quantitative (1x1 meter2). The results showed that 22 species were found, ie. 14 species (belong to 5 family) of Infra Order Brachyura, 4 species (belong to 4 family) of Infra Order Macrura, 3 species Isopoda and one species Copepod. Diversity index revealed that all stations had medium category Uniformity index showed that station A and D had high category, station B and C had stations is low category. There were no dominance at Stations A and D, but Station B and C were dominated by Cerapus sp. Most of crustaceans was clumped distributed. High community similarity index values showed by Station A-B, A-C, B-C but low at Stations A-D, B-D, C-D). Generally, among Brachyuran, male greater number than females, and 23.07% gravid females were found.